Mecanismo de ação molecular envolvido na captação de Ca2+ de compostos presentes na Cecropia glaziouii Sneth (procianidinas, flavanóis e flavonóides) em culturas de células musculares lisas vasculares e células endoteliais - Dermondes, Gabriella Trettel [UNIFESP] (2020)
The vast majority of drugs used in therapy derived from active products taken from nature. Cecropia glaziouii Sneth is a tree typical of tropical and subtropical regions of Latin America, and is widely used in folk medicine. Previous studies from our group demonstrated that the aqueous extract (EA) of Cecropia glaziouii Sneth and its butanolic fraction (FBut) have hypotensive and antihypertensive activities which were related to relaxation of vascular smooth muscle by in vitro experiments. The same activitieswere obtained after oral chronic administration of EA and FbutBased on these data, this work aims to analyze the molecular mechanisms of action of compounds present in C. glaziouii Sneth in calcium mobilization by cultured vascular smooth muscle and endothelial cells. The mechanisms of action of the following major Cecropia compounds were analyzed in calcium mobilization, by spectrophotofluorimetry: isovitexine, isoorientine, catechin, epicatechin, procyanidin B2, procyanidin B3 and orientin. The results were obtained, by comparison with agonists (KCl, ACh, Ang II and BK) and antagonists (verapamil, atropine, losartan and HOE140) with known mechanisms of action. It was verified that Cecropia compounds influence the mobilization of intracellular calcium in both cell types. In endothelial cells, all compounds tested, except isoorientin, act similarly to verapamil, blocking L-type calcium channels; and the compounds isovitexin, epicatechin and procyanidin B3 have a mixed effect, also acting through the muscarinic pathway via activation of M3 metabotropic receptors. All compounds, except isoorientin, act in the pathway involving AT1 receptors, since their activity were blocked by losartan, while isovitexin, isoorientin, epicatechin and procyanidin B3 present an effect on calcium mobilization via NO pathway, since their action was blocked by the antagonist HOE 140. In vascular smooth muscle cells, the observed effect suggests that the all the tested compounds act via L-type calcium channels. In the case of isovitexin and isoorientin this effect was associated with an action involving AT1 receptors. In conclusion the tested compounds present in Cecropia glaziouii Sneth, tested in cultured endothelial and vascular smooth muscle cells, mostly present a mixed mechanism of action on intracellular calcium mobilization, acting in more than one pathway involved in justifying the popular antihypertensive use of the plant.